Structure behind principles: social selection mechanisms in corporate governance networks. Issue 1 (23rd October 2019) - Kacanski, Slobodan
Abstract : Purpose: The purpose of this study is to show that social relations in a corporate governance platform between members of supervisory boards and between members of supervisory and executive board tiers can serve as an alternative viewpoint for understanding mechanisms of social selection in corporate governance networks. The study shows that through the lenses of social network analysis, it is possible to identify and understand how the process of corporate governance member selection unfolds within companies and how that selection process may have been potentially influenced by the cross-board relations, such as interlocking directorships. Design/methodology/approach: To estimate network parameters and attribute effects of network tie emergence, this study has used exponential random graph models (ERGMs) on corporate governance data of Danish publicly listed companies. Econometric models are applied to estimate parameter statistics which serve further to explain tendencies of tie emergence. Findings: The results of this study reveal that the process of selection of both supervisory boards and executive directors is interdependent. Also, the study showed that board members are more likely to select popular supervisory board members and top managers who have their expertise gained through multiple companies affiliated with multiple industries. However, these conditions for CEO selection apply only to the extent to which they have their experience gained from multiple companies but not multiple industries. Originality/value: On one hand, this study demonstrates that being a dynamic practitioner who is exposed to diverse corporate environments by being affiliated with different companies belonging to different industries generally increases practitioners visibility in the corporate governance network, and therefore their attractiveness to boards of directors. On the other hand, the results show that the research on board assemblage, nowadays, should be rather observed through the methodology of social network analysis as the method gives an opportunity to understand structures through relations, from which the executive tier should not be exempted as well.